Conceptual and Historical Analysis of Sociolinguistics as an Interdisciplinary Science - Habiburahman; Muhamad Zamzam Mubarok; Izzuddin; Ade Nandang (DIROSAT: Journal of Education, Social Sciences & Humanities, 2026)
This article explores the development of sociolinguistics as an interdisciplinary field that examines the relationship between language and society. Sociolinguistics emerged from the integration of linguistics, which studies the structure of language, and sociology, which investigates the structure of social interaction. The aim of this study is to describe how language is used in specific social contexts and how social, cultural, and psychological factors influence language use. This research employs a descriptive qualitative method with a library research approach. Data were collected from books, scholarly journals, and works by prominent scholars such as Ferdinand de Saussure, Dell Hymes, and Joshua Fishman. The discussion includes the definition of sociolinguistics, its historical development, and the scope of study, including language variation, code-switching, code-mixing, social identity, and the role of language in social institutions. The findings show that sociolinguistics plays a vital role in bridging our understanding of linguistic dynamics and social interaction. Beyond its theoretical significance, sociolinguistics also offers practical benefits in education, language policy, and intergroup communication within multilingual societies.